Melting experiments on peridotite to lowermost mantle conditions. Issue 6 (24th June 2014) - Tateno, Shigehiko; Hirose, Kei; Ohishi, Yasuo
Abstract Melting experiments on a pyrolitic mantle material were performed in a pressure range from 34 to 179 GPa based on laser‐heated diamond‐anvil cell (DAC) techniques. The textural and chemical characterizations of quenched samples were made by using field‐emission‐type electron microprobe (FE‐EPMA). Melts formed by 46 to 77 wt.% partial melting in this study were ultrabasic in composition and became more depleted in SiO2 and more enriched in FeO with increasing pressure. Melting textures indicate that the liquidus phase changed from ferropericlase to MgSiO3‐rich perovskite at least above 34 GPa and further to post‐perovskite. The first phase to melt (disappear) changed from CaSiO3 perovskite to (Mg, Fe)O ferropericlase between 68 and 82 GPa. The stability of ferropericlase above solidus temperature shrinks with increasing pressure (melting last below 34 GPa and first 82 GPa), resulting in higher (MgO + FeO)/SiO2 ratio in partial melt at higher pressure. Additionally, the Fe‐Mg distribution coefficients (KD) between perovskite/post‐perovskite and melt decreased considerably with increasing pressure, leading to strong Fe‐enrichment in partial melts. It supports dense partial melts in a deep lower mantle, which migrate downward to the core mantle boundary (CMB).